EXPLORING THE LANGUAGE LEARNING STRATEGY AND FOREIGN LANGUAGE LEARNER’S SELF-EFFICACY ON ENGLISH LANGUAGE STUDENT TEACHERS - Diah Yovita Suryarini; Reza Syehma Bahtiar (Widya Mandala Surabaya Catholic University, 2021)
This study aims to investigate the language learner’s strategy that frequently use by the student teachers, foreign language learner’s self-efficacy level and the relationship that may occur between the language learning strategy and the student teacher’s foreign language learner’s self-efficacy. Accordingly, this study is not only to find out the strategy used and the level of foreign language learner’s self-efficacy, but also to find out whether there is positive relationship between them. This study is a quantitative descriptive study with case study approach since the sample of this study is less than one hundred people. The subject of this study is the English language student teachers that have taken all four skills courses. The sample of this study are fifteen student teachers of English. This study used two questionnaires to collect the data. First: Strategy Inventory for Language Learning (SILL) that was used to collect the data of language learning strategy. While the second one is Foreign Language Learner’s Self-Efficacy Questionnaire that was used to measure the level of foreign language learner’s selfefficacy. Furthermore, the data were analyzed quantitatively using SPSS 21 to find out whether the two factors have relationship. The result of this study showed that the language learning strategy that commonly use by the student teachers is social strategy and followed respectively by metacognitive strategy, cognitive strategy, and affective strategy. Regarding the level of self-efficacy, the result showed that the English language student teacher have high self-efficacy which may be related to they are being students (may be because they are the student teacher of English) and English is their major study therefore they might have more competent in English. Furthermore, the result of this study also showed that there was a positive relationship between English language learning strategy and Foreign language learner’s self-efficacy. The use of language learning strategy can heighten the student teachers’ language learner self-efficacy.